INCREASE ENGLISH CHILDREN VOCABULARY SKILLS THROUGH ACTIVE PLAYING STRATEGIES - Nining Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2019)
One of the goals in implementing English learning in kindergarten is to foster children's interest in learning English. Early English mastery cannot be compared to adults. English for early childhood is only limited to the introduction of vocabulary that is often found in the environment. In teaching English vocabulary in kindergarten, it must be fun to do so that children are not bored. Therefore, researchers conduct research using active play strategies in order to create interesting and fun learning for children. This class action research was carried out on children of group B of Aisyiah Kindergarten, Widodaren District, Ngawi City. The results showed that active play strategies can improve children's English vocabulary skills.